The socialization of bibliographic and documentary heritage of humanity from the perspective of the cultural rights - Palma Peña, Juan Miguel (Revista General de Información y Documentación, 2012)
The socialization of cultural expressions refers to society having access, knowing, appreciating, and reasonably using cultural events and documentaries worldwide. Cultural rights are inherent attributes of society that enable cultural value, experiential demonstrations and reasonably tangible and intangible representations. From this understanding, cultural rights are conducive to socializing the documentary heritage because -among other contributions- they provide access to information, the assessment of documents and the preservation of information in all its manifestations. The overall objective of this document is to analyze some key to socialize bibliographic and documentary heritage of humanity. The particular aim of this paper is to reflect on the socialization of documentary heritage from the viewpoint of the cultural rights, educational trends related to the rights and heritage, and the action on the issue from a library science approach. This document is divided into four sections. The first addresses the fundamental concepts of bibliographic and documentary heritage. The second contains the corresponding to the socialization of the documentary memory. The third is the relationship between cultural rights, libraries and documentary heritage. Finally, we analyze the mission of librarians regarding the socialization of documentary heritage.